Life cycle assessment of motor oil as a sustainable product in Santander (REVISTA AMBIENTAL AGUA, AIRE Y SUELO, 2013)
The life cycle assessment of motor oil as a sustainable product in Santander was carried out under the LCA LifeCycleAssessment standard, set forth by ISO 14040. As stated in the standard, the “cradle-to-grave” stages were taken into account in order to obtain complete and accurate information about the process. The stages taken into account during the information gathering process were the inputs, which included the raw materials used, manufacturing and production, and finally recycling and environmental impact. The study provides an overview of the problems existing in the region and new alternatives based on the assessment and conclusions of the study.
Keywords: life cycle; motor oil; sustainable products